New Quality College Students from the Perspective of New Productive Forces：Connotation, Characteristics and Transformation of Cultivation Paradigms - Liu, Liming; Liu, Minwen; Syarizal, Abdul Rahim; Huang, Qihua; Chen, Zaidie (INTI International University, 2025)
In the context of profound economic and social transformation driven by new productive forces, this article proposes the core concept of "new quality college students" to address the urgent need for strategic adjustments in the talent development paradigm of higher education. The present study firstly analyses the connotations of new productive forces and its core requirements for human capital, i.e. innovation, versatility, strategic thinking and adaptability. Moreover, it systematically defines the core concept of "new quality college students" and summarizes their four defining characteristics. The article's core argument focuses on how new productive forces can fundamentally drive a profound paradigm shift in higher education across training objectives, curriculum systems, teaching models, evaluation mechanisms, and governance ecosystems. This article proposes a training system for college students that is intended to produce a new type of student. This system is based on a "concept-pathway-guarantee" framework. This study takes a three-pronged research approach: "theoretical construction, practical analysis, and innovative approaches". The aim of this framework is to provide theoretical guidance and a practical framework for building a future-oriented, world-class higher education system with Chinese characteristics. At the same time, it makes beneficial contributions to the theoretical and practical exploration of higher education worldwide.